2020
DOI: 10.1126/sciadv.aba2084
|View full text |Cite
|
Sign up to set email alerts
|

Cellular diversity of the regenerating caudal fin

Abstract: Zebrafish faithfully regenerate their caudal fin after amputation. During this process, both differentiated cells and resident progenitors migrate to the wound site and undergo lineage-restricted, programmed cellular state transitions to populate the new regenerate. Until now, systematic characterizations of cells comprising the new regenerate and molecular definitions of their state transitions have been lacking. We hereby characterize the dynamics of gene regulatory programs during fin regeneration by creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 63 publications
2
63
0
Order By: Relevance
“…We also identified genes with significantly increased expression in 3). This included cdh11 (Fig 1H ), which was recently identified by scRNA-seq to be a potential marker of osteoblastic cells, but still remains to be validated [18]. We concluded that osteoblast1 and osteoblast2 were enriched for cells fated to become osteoblasts and joint cells, respectively.…”
Section: Sci-rna-seq Captures Rare Osteoblastic Populationsmentioning
confidence: 67%
See 1 more Smart Citation
“…We also identified genes with significantly increased expression in 3). This included cdh11 (Fig 1H ), which was recently identified by scRNA-seq to be a potential marker of osteoblastic cells, but still remains to be validated [18]. We concluded that osteoblast1 and osteoblast2 were enriched for cells fated to become osteoblasts and joint cells, respectively.…”
Section: Sci-rna-seq Captures Rare Osteoblastic Populationsmentioning
confidence: 67%
“…As such, more in-depth molecular characterizations are needed. While single cell analyses are comprehensive approaches and can provide valuable insight, previous single-cell RNA-seq (scRNA-seq) studies of zebrafish caudal fin regeneration have reported low numbers of osteoblastic cells [18], preventing an in-depth analysis of E and M characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Fibin transcripts are also decreased in lung samples of mice exposed to house dust mite, Toxoplasma, or influenza, RSV, and SARS-Cov viruses. Analysis of single cell RNA seq datasets in zebrafish (caudal fin; [64]) and the human lung (IPFcellatlas.com) also revealed that zebrafish fibina, fibinb and human FIBIN are expressed in the mesenchymal lineage, specifically in fibroblasts (not shown). Consistent with the expression of FIBIN in lung fibroblasts and with the decrease of Fibin transcripts in mouse models of lung damage, we found that mesenchymal FIBIN expression is decreased in lung samples from patients with chronic lung conditions such as IPF and asthma (Fig.…”
Section: Datamining Of Fibin Expression In Various Models Of Injury Amentioning
confidence: 99%
“…Moreover, establishing new experimental systems to segregate wound healing and the onset of tissue regeneration will also be valuable. Furthermore, emerging new technologies, such as single cell sequencing and various “omics”, have already been applied to regenerative species such as axolotls and zebrafish (Gerber et al 2018 ; Leigh et al 2018 ; Hoang et al 2020 ; Hou et al 2020 ; Li et al 2020 ), and will contribute to in-depth study of the current unresolved issues in the field of regeneration.…”
Section: Introductionmentioning
confidence: 99%